Boosting Hydrogen Evolution Reaction on Co9S8 in Neutral Media Leveraging Oxophilic CrOx Mosaic Dopant - Park, Yeji; Kim, Hong Ki; Kwon, Taehyun; Jun, Minki; Kim, Doyeop; Kim, Taekyung; Kim, Byeongyoon; Baik, Hionsuck; Kim, Ki-Jeong; Lee, Ji Yeong; Kim, Jin Young; Baik, Mu-Hyun; et al. (Wiley-VCH Verlag, 2025)
The electrochemical production of sustainable hydrogen under neutral conditions is advantageous, as it allows for the use of wastewater or seawater without the need for pH adjustments. However, the low ion concentration in neutral electrolytes typically results in limited adsorption of reactants on the catalyst surfaces, leading to sluggish reaction kinetics. Therefore, enhancing absorption capacity is a key challenge in the development of neutral hydrogen evolution reaction (HER) catalysts. Hetero-structured catalysts may improve surface adsorption through extensive interfacing between phases, enabling active transportation of reaction intermediates. Integrating metal sulfides and oxides, in particular, holds the potential for generating efficient electrocatalysts with improved HER activity and surface adsorption capacity. Herein, the synthesis of CrOx-doped Co9S8/CuCrS2 mosaic hetero-nanostructures is reported as a proficient HER catalyst. Facile Cr-cation migration at the Co9S8/CuCrS2 interface enables the preparation of Cr-oxide sub-nano domains within the sulfide matrix, boosting the HER catalysis in neutral media. The exceptional electrochemical performance is demonstrated in a pH 7.4 phosphate buffer solution, including low overpotential, small Tafel slope, and stability over 60 h. The formulation of catalyst design and synthetic approaches has the potential to pave the way for diverse catalytic applications utilizing metal oxide-doped hetero-nanostructures.